2006
DOI: 10.1177/0146167206291475
|View full text |Cite
|
Sign up to set email alerts
|

Why Are Attributions to Discrimination Interpersonally Costly? A Test of System- and Group-Justifying Motivations

Abstract: be achieved without considering the interpersonal consequences of these judgments. We first describe these interpersonal consequences and then integrate this research within a theoretical framework examining how system-and group-justifying beliefs moderate these consequences. Interpersonal Nature of Discrimination AttributionsIn the first investigation documenting the interpersonal consequences of discrimination attributions, Kaiser and Miller (2001) had White participants read about a Black man who received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 50 publications
10
111
0
2
Order By: Relevance
“…Allocating blame exclusively to the evaluator may explain why the results of the present study differed from prior research. Finally, recent research by Kaiser et al (2006) found that overall, Whites did not evaluate a Black target who claimed discrimination more negatively than a Black target who claimed unfairness. However, Whites who endorsed systemjustifying beliefs (e.g., those who indicated that the world is fair) did rate the Black target who blamed his outcome on discrimination more negatively than the Black target who blamed general unfairness.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Allocating blame exclusively to the evaluator may explain why the results of the present study differed from prior research. Finally, recent research by Kaiser et al (2006) found that overall, Whites did not evaluate a Black target who claimed discrimination more negatively than a Black target who claimed unfairness. However, Whites who endorsed systemjustifying beliefs (e.g., those who indicated that the world is fair) did rate the Black target who blamed his outcome on discrimination more negatively than the Black target who blamed general unfairness.…”
Section: Discussionmentioning
confidence: 90%
“…Feminist ideology implies that the world is not a fair, just place. Kaiser et al (2006) demonstrated that the more participants endorsed American dominant ideology (i.e., Protestant work ethic, belief that the world is just and fair), the more threatened they felt when they read that an African-American made a claim of discrimination. In the present study, participants' worldviews may have been threatened when the woman was described as a feminist, and perhaps it would be even more threatening to acknowledge that such a woman actually did face discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People generally have a need to defend their personal worldview. In particular, white people, as a high-status group, are likely to justify their worldview in terms of the status quo and to react defensively to threats against that view (Jost, 2006;Kaiser, Dyrenforth, & Hagiwara, 2006). However, strongly identified black people (a low-status group) are prone to be dissatisfied with their position and to assert the illegitimacy of the current status hierarchy.…”
Section: Group Identity Of Outgroup Members and Anticipated Rejectionmentioning
confidence: 99%
“…For instance, individuals who publicly attribute negative outcomes to discrimination can be perceived more negatively, even by members of their own group. This results in stigmatized individuals being less likely to make claims of discrimination for fear of negative consequences, despite the positive effects of making such claims (e.g., Kaiser, Dyrenforth, & Hagiwara, 2006;. This makes reacting to discrimination even more difficult for targets of discrimination.…”
Section: Attributions To Discrimination As a Moderatormentioning
confidence: 99%